Ciphertext-Policy Attribute Based Encryption with Selectively-Hidden Access Policy - Arkin, Gulmire; Helil, Nurmamat (Computing and Informatics, 2021)
In conventional Ciphertext-Policy Attribute-Based Encryption (CP-ABE), the access policy appears in plaintext form that might reveal confidential user information and violate user privacy. CP-ABE with hidden access policies hides all attributes, but the computational burden increases due to the attribute hiding. In this paper, we present a Linear Secret Sharing Scheme (LSSS) access structure CP-ABE scheme that hides only sensitive attributes, rather than all attributes, in the access policy. We also provide an attribute selection method to choose these sensitive attributes and use an Attribute Bloom Filter (ABF) to hide them. Compared with the existing major CP-ABE schemes with hidden access policies, our proposed scheme is flexible in selecting attributes to hide. This scheme enhances the efficiency of policy hiding while still protecting policy privacy. Test results show that our approach is reasonable and feasible.